Progressive Muscle Relaxation Terhadap Perubahan Kadar Glukosa Darah Pada Pasien Diabetes Melitus di RS Bhayangkara TK. I Pusdokkes Polri - Aprisunadi, Aprisunadi; Jamiatun, Jamiatun; Ifadah, Erlin; Kalsum, Umi; Nugraha, Agung Tri; Hidayah, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Diabetes Mellitus (DM) is a chronic disease characterized by elevated blood glucose levels due to the body's inability to produce sufficient insulin or its inability to utilize insulin optimally. Diabetes can be managed pharmacologically or non-pharmacologically. One non-pharmacological method that has been proven effective in helping control blood sugar levels is progressive muscle relaxation therapy. This therapy is known to reduce peripheral vascular resistance and increase blood vessel elasticity. Furthermore, progressive muscle relaxation therapy also provides significant relaxation effects for DM sufferers. This community service activity was conducted at the Bhayangkara Hospital, TK.I, Pusdokkes Polri, involving 10 DM patients as participants. The activity was carried out through counseling and hands-on practice. During the progressive muscle relaxation session, patients appeared enthusiastic and participated in the exercises. Observations showed that 95% of participants were in the very good category in performing the progressive muscle relaxation technique. It is hoped that through this activity, diabetes sufferers can apply it independently at home to help control blood sugar levels. Keywords: Diabetes Mellitus, Progressive Muscle Relaxation, Blood Sugar